A Polymerized‐Ionic‐Liquid‐Based Polymer Electrolyte with High Oxidative Stability for 4 and 5 V Class Solid‐State Lithium Metal Batteries (Adv. Energy Mater. 27/2022). Issue 27 (21st July 2022) - Fu, Chengyin; Homann, Gerrit; Grissa, Rabeb; Rentsch, Daniel; Zhao, Wengao; Gouveia, Tom; Falgayrat, Anaïs; Lin, Rongying; Fantini, Sébastien; Battaglia, Corsin
Abstract : Polymer Electrolytes In article number 2200412, Chengyin Fu and co‐workers develop a nonflammable polymer solid electrolyte, based on a low‐cost polymerized ionic liquid, with a high room‐temperature ionic conductivity of 0.8 mS cm −1 and a high oxidative stability > 5.0 V vs Li + /Li. The electrolyte enables high‐performance solid‐state lithium metal batteries with a high‐energy uncoated LiNi0.8 Mn0.1 Co0.1 O2 cathode and a high‐voltage LiMn1.5 Ni0.5 O4 cathode at room temperature.